El Derecho a la vivienda: problemas, regulación y retos en el contexto peruano - Ortiz Sánchez, Iván; Vílchez Vargas, Ximena (Pontificia Universidad Católica del Perú, 2023)
Is the Right to Adequate Housing recognized in the Peruvian Political Constitution of 1993? What has the Constitutional Court ruled regarding this Right? How may the Public Law help to overcome the challenges imposed by the need to guarantee the Right to Adequate Housing? This article tries to answer these questions by analyzing the regulation of the Right to Adequate Housing in international treaties and instruments applicable to our country, and the national regulation and jurisprudence. The last section will reflect on the challenges to the Right to Adequate Housing under the framework created by the National Housing and Urban Policy (2021) and the Act 31313, Sustainable Urban Development Act.

¿El Estado peruano reconoce el derecho a la vivienda adecuada en nuestra actual Constitución Política? A través del desarrollo jurisprudencial, ¿qué nos dice el Tribunal Constitucional sobre este derecho? ¿Cuáles son los retos del derecho a la vivienda vinculados con el Derecho Administrativo? El presente artículo busca dar respuesta a estas interrogantes a partir de la revisión de diversos instrumentos internacionales de los cuales el Perú es un Estado parte; así como de la revisión de la normativa interna y jurisprudencia peruana. Finalmente se reflexionará sobre los retos que tiene el derecho a la vivienda en el contexto peruano a partir de la reciente publicación de la Política Nacional de Vivienda y Urbanismo (2021) y la Ley 31313, Ley de Desarrollo Urbano Sostenible.
Right to housing: Problems, Regulation and Challenges in the Peruvian context
Keywords: Human Rights; Right to Adequate Housing; Social Housing; Housing shortage; Urban development; National Housing and Urban Policy; Derechos humanos; Derecho a la vivienda; Vivienda de interés social; Déficit habitacional; Desarrollo urbano; Política Nacional de Vivienda y Urbanismo; https://purl.org/pe-repo/ocde/ford#5.06.00